Abusive supervision, public service motivation, and employee deviance: The moderating role of employment sector. Issue 3 (5th December 2016) - Vogel, Rick; Homberg, Fabian; Gericke, Alena
Abstract : Purpose: The purpose of this paper is to examine abusive supervision and public service motivation (PSM) as antecedents of deviant workplace behaviours. Design/methodology/approach: The study was conducted in a cross-sectional research design with survey data from 150 employees in the public, private, and non-profit sector in Germany and the USA. Findings: Abusive supervision is positively associated with employee deviance, whereas PSM is negatively related to deviant behaviours. The employment sector moderates the negative relationship between PSM and employee deviance such that this relationship is stronger in the public and non-profit sector. Research limitations/implications: Limitations arise from the convenience sampling approach and the cross-sectional nature of the data set. Practical implications: Human resource managers should consider behavioural integrity in the attraction, selection, and training of both supervisors and subordinates. Private organisations can address the needs of strongly public service motivated employees by integrating associated goals and values into organisational missions and policies. Originality/value: This is the first study to introduce PSM into research on employee deviance. It shows that a pro-social motivation can drive anti-social behaviours when employees with high levels of PSM are members of profit-seeking organisations.